Analysis of the Influence of Problem Based Learning Models Assisted by Wordwall Media on Science Learning Outcomes of Primary School Students - Alifia Citra Syaifi; Susanti Murwitaningsih (Jurnal Paedagogy, 2022)
This study aims to analyze the effect of the Problem Based Learning model assisted by Wordwall media in thematic learning of science content on force and motion material on the learning outcomes of fourth-grade students at SDN Pasir Putih 03. This quantitative research design, True Experiment, used a posttest-only control group final test. Cluster random was the sampling used. Biserial Point Correlation was used to test the validity and produces 25 valid questions and five drop questions from a total of 30 multiple-choice questions. The KR-20 was used to test reliability and get rcount = 0,75 > rtable = 0,34 so the instrument is reliable. Liliefors test in order to test normality obtained values for the control class and experimental class, namely Lcount = 0,1467 < Ltable = 0,152 and Lcount = 0,0972 < Ltable = 0,152 which means that both data were normally distributed. Fisher's test is used to test the homogeneity and get homogeneous results, namely Fcount = 1,67 < Ftable = 1,79. T-test to test the hypothesis of tcount = 8,97 > ttable = 1,668 at 0.05 with dk = 66. Then H0 was rejected, and H1 was accepted, namely the influence of problem-based learning models assisted by Wordwall media in thematic learning of science content on force and motion material on the learning outcomes of fourth-grade students at SDN Pasir Putih 03. The results of this study showed that the use of the PBL model could make students more active, think critically, and independent. Where with this model, students are required to find their solutions to problems by conducting an experimental, and with the help of website-based Wordwall media, students become more enthusiastic and not bored because, with the help of this media, students can learn while playing.